2021
DOI: 10.3390/children8040292
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Post-Stroke Consequences in Pediatric Ischemic Stroke in the Context of Neuroimaging Results—Experience from a Single Medical Center

Abstract: Arterial ischemic stroke (AIS) in children is a rare condition; its frequency is estimated at 0.58 to 7.9 new onsets in 100,000 children per year. The knowledge on risk factors, clinical outcomes and consequences of pediatric AIS is increasing. However, there are still many unknowns in the field. The aim of the study was to analyze the clinical presentation of pediatric AIS and its consequences according to the neuroimaging results and location of ischemia. The research was retrospective and observational. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Nine studies [3][4][5][6][7][8][9][10][11] were identified with 1328 stroke patients. 9/9 studies showed association of frontal lobe involvement with higher likelihood of PSE (OR=2.10, 95% CI=1.37-3.21, p-value=0.0007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies [3][4][5][6][7][8][9][10][11] were identified with 1328 stroke patients. 9/9 studies showed association of frontal lobe involvement with higher likelihood of PSE (OR=2.10, 95% CI=1.37-3.21, p-value=0.0007).…”
Section: Resultsmentioning
confidence: 99%
“…The number of the patients were directly obtained or derived from the available information in the manuscripts of the included studies. With a study that specified concurrent involvement of different lobes (Kopyta 2021), e.g. frontal only vs frontal, temporal, and parietal, the cases with frontal lobe involvement were added, and the cases with no involvement of frontal lobe were added to evaluate for the association of frontal lobe infarcts and poststroke epilepsy.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…The odds of poststroke seizures in females with total anterior circulation infarct (TACI) and posterior circulation infarct (POCI) were eight-fold higher than in females with lacunar anterior circulation infarct (LACI) and partial anterior circulation infarct (PACI) stroke (odds ratio (OR): 8.62). Girls with TACI were also more likely to develop seizures than boys with TACI (56% vs. 28%) [ 12 , 13 ].…”
Section: Review Outlinementioning
confidence: 99%
“…This Special Issue brings together two original research papers, as well as three literature reviews, on a variety of topics related to pediatric arterial ischemic stroke. The first original research by Kopyta et al [ 4 ] carried out a retrospective analysis on clinical presentation of pediatric AIS and its consequences according to the neuroimaging results and location of ischemia in a group of 75 pediatric patients. The study demonstrates a correlation between the presence of a specific post-stroke result and the location of vascular or morphological changes observed in neuroimaging.…”
mentioning
confidence: 99%
“…Post-stroke epilepsy and aphasia have been observed with the same frequency in patients with changes in the temporal lobe. In turn, 6% of patients with changes in the temporal lobe presented movement disorders other than hemiparesis, and 3% had intellectual retardation [ 4 ].…”
mentioning
confidence: 99%